2021
DOI: 10.3390/met11020295
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching of Pyrrhotite with Bacterial Adaptation and Biological Oxidation for Iron Recovery

Abstract: The microbially mediated recovery of valuable metals contained in mining waste presents an economical alternative to conventional hydrometallurgical processes. In order to investigate the effect of bacterial adaptation and biological oxidation on bioleaching, the microbially mediated bioleaching of a pyrrhotite sample from mine waste, with indigenous bacteria existing in acid mine drainage, was studied. The indigenous bacteria were sub-cultured repeatedly for iron adaptation, and Acidithiobacillus ferrooxidans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Studies in the literature have shown that bioleaching is efficient for the extraction of metals from water treatment sludge (Cr 92.6%, Cu 80.6%, Fe 95.6%, Mg 91%, Ni 89.7%, Pb 99.5%, Zn 93% [ 33 , 34 , 35 ], Fe 76.5%, Cu 82%, Pb 89.9%, Zn 90%) [ 31 ] or from municipal and industrial waste [ 36 ]. Pyrotite bioleaching could increase Fe recovery by bacterial adaptation and biological contact oxidation [ 37 ], and Fe can be removed (18%) by adding 9K medium [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the literature have shown that bioleaching is efficient for the extraction of metals from water treatment sludge (Cr 92.6%, Cu 80.6%, Fe 95.6%, Mg 91%, Ni 89.7%, Pb 99.5%, Zn 93% [ 33 , 34 , 35 ], Fe 76.5%, Cu 82%, Pb 89.9%, Zn 90%) [ 31 ] or from municipal and industrial waste [ 36 ]. Pyrotite bioleaching could increase Fe recovery by bacterial adaptation and biological contact oxidation [ 37 ], and Fe can be removed (18%) by adding 9K medium [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, oxygen solubility differs in various solutions. Iron ions are particularly important among various metal ions in the growth environment of A. ferrooxidans ( Kim et al, 2021 ). Fe 2+ is a necessary component of growth media from which Fe 3+ -rich leaching liquors are generated.…”
Section: Introductionmentioning
confidence: 99%
“…mg/L)[40]. Sphalerite: ZnS + 0.5O 2 + H 2 SO 4 → ZnSO 4 + H 2 O + S (2) O 2 + 2H 2 SO 4 → 2Fe 2 (SO 4 ) 3 + 2H 2 O (7) (Zn Pb Fe Cu)S + Fe 2 (SO 4 ) 3 → (Zn Pb Fe Cu)SO 4 + 2FeSO 4 + S (8)…”
mentioning
confidence: 99%